Morphological characterization and phylogenetic analysis of aeroterrestrial Vischeria/Eustigmatos strains with industrial potential. Issue 1 (1st January 2019) - Stoykova, Petya; Stoyneva-Gärtner, Maya; Uzunov, Blagoy; Gärtner, Georg; Atanassov, Ivan; Draganova, Petya; Borisova, Cvetanka
Abstract: Microalgae are subject of extensive scientific and commercial interest in terms of both fundamental ecology and biotechnological potential. Here, we describe five Bulgarian aeroterrestrial strains of the Eustigmatos/Vischeria group, which have shown potential as valuable carotenoid producers. The strains are stored in the algal collection of Sofia University (ACUS). The main cytological and morphological diagnostic features of the studied eustigmatophycean stramenopile algae remained stable during long-term cultivation, showing that immediate light microscopy (LM) identification in cultures is reliable. We used a polyphasic approach for taxonomical identification, combining conventional microscopy of culture material with molecular-genetic methods (based on rbcL gene sequencing). This approach led to almost similar taxonomic results, supporting the need for unification of the genera Eustigmatos and Vischeria (which are presently separated on the basis of morphological features). Based on the obtained results, we speculate that there could be new eustigmatophyceaen aeroterrestrial taxa. This, however, needs to be confirmed in more refined molecular-genetic studies with a view to exploiting the full biotechnological potential of the aeroterrestrial Eustigmatos/Vischeria strains described here.